2005
DOI: 10.1159/000086206
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia with 100% Oxygen following Hypoxia-Ischemia Increases Brain Damage in Newborn Rats

Abstract: Objective: To describe the effect of reoxygenation with 100% O2 as compared to the effect of room air in newborn rat brains after asphyxia. Methods: Experimental asphyxia (carotid artery ligation followed by hypoxic exposure with 8% O2 for 2 h) was performed on 7-day-old rats. After hypoxia-ischemia the rats were reoxygenated with either 100% O2 (hyperoxia group) or 21% O2 (room air group) for 24 h and then returned to the dam. The rats were killed 1 week after the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Several groups have found increased brain lesions in neonatal rats after hyperoxic reoxygenation following HI (25,38,39). The increased inflammatory gene response after hyperoxic reoxygenation we found in the present study, supports the evidence that increased inflammation might be one of the contributing factors to the increased brain damage after hyperoxic reoxygenation.…”
Section: Igf1rsupporting
confidence: 91%
“…Several groups have found increased brain lesions in neonatal rats after hyperoxic reoxygenation following HI (25,38,39). The increased inflammatory gene response after hyperoxic reoxygenation we found in the present study, supports the evidence that increased inflammation might be one of the contributing factors to the increased brain damage after hyperoxic reoxygenation.…”
Section: Igf1rsupporting
confidence: 91%
“…The volume of the hyperintense lesions after HHI was significantly larger compared to HI alone (3 weeks PI, Fig. 2) similarly to results reported elsewhere for one day post-injury (Gill et al, 2008) that showed larger cortical damage than previous reports (Shimabuku et al, 2005) where there was brain damage in 42% of rats treated with HHI and 13% of those treated with HI. We report that HI caused lesions in 60% of rats and HHI caused lesions in 100% of all rats.…”
Section: Injury After Hhisupporting
confidence: 89%
“…A guideline for the treatment of acute perinatal hypoxia is resuscitation with 100% oxygen (hyperoximia) (Niermeyer et al, 2000). It has been reported that in experimental perinatal hypoxia, acute hyperoximic treatment exacerbates the initial injury (Munkeby et al, 2004;Shimabuku et al, 2005). Hu et al (2003) reported that hyperoximia in rats triggers an additional apoptotic signaling pathway when compared to hypoxia alone.…”
mentioning
confidence: 99%
“…Similarly, in other studies, the duration of postischemic reoxygenation with use of pure oxygen varies from 5 min to 24 h regardless of the resuscitation-induced changes in CBF (4,5,25). This may limit the clinical value of experimental data.…”
mentioning
confidence: 95%
“…Perhaps, significantly worse geotaxis reflex performance in Re-O 2 mice is related to this pathophysiological sequence. Physiologically unjustified, prolonged (24 h) use of pure O 2 after restoration of O 2 tissue delivery has been shown to adversely affect postHI recovery in neonatal rats (25).…”
mentioning
confidence: 99%